Identity fusion, outgroup relations, and sacrifice: A cross-cultural test - Purzycki, Benjamin Grant; Lang, Martin (Cognition, 2019)
Identity fusion theory has become a popular psychological explanation of costly self-sacrifice. It posits that while maintaining one's own individual identity, a deep affinity with one's group can contribute to sacrifice for that group. We test this and related hypotheses using a behavioral economic experiment designed to detect biased, self-interested favoritism among eight different populations ranging from foragers and horticulturalists to the fully market-integrated. We find that while individuals favor themselves on average, those with higher ingroup fusion sacrifice more money to other members of their ingroup who are unable to reciprocate. We also find that positive outgroup relations has a similar effect. Additionally, we assess a recently-posited interaction between ingroup and outgroup relations and show no consistent effect at the individual or sub-sample levels.
Keywords: Cooperative Behavior; lidé; Models, Psychological; srovnání kultur; Humans; skupinové procesy; Identity fusion; kooperační chování; Sacrifice; behaviorální ekonomie; Cross-Cultural Comparison; Intergroup dynamics; interpersonální vztahy; sebepojetí; psychologické modely; Self Concept; Economics, Behavioral; Cooperation; Group Processes; Interpersonal Relations